INTERNSHIP EXPERIENCE AND WORK INTEREST AS PREDICTORS OF WORK READINESS AMONG OFFICE AUTOMATION AND MANAGEMENT VOCATIONAL STUDENTS - Wijaya, Rama Surya; Purwana, Dedi; Suherdi (Jurnal Pendidikan Ekonomi, Perkantoran, dan Akuntansi, 2025)
The background of this study is based on the importance of vocational high school students' work readiness in facing the world of work after graduation, considering the strategic role of vocational education in producing a skilled and ready-to-use workforce. This study aims to determine the effect of internship experience and work interest on the work readiness of students majoring in Office Automation and Management (OTKP) at SMKN 50 Jakarta. This study uses a quantitative approach with a survey method and data collection techniques through questionnaires. The population in this study were all OTKP students of SMKN 50 Jakarta in the 2024/2025 academic year, with a total sample of 108 students being sampled using total sampling. Data were analyzed using SmartPLS software. The results show that both internship experience and work interest have a significant influence on students' work readiness. Internship experience contributes to students' understanding of the world of work, while work interest encourages students' mental readiness and motivation to immediately enter the world of work.